Glycoalkaloids of Wild and Cultivated Solanum: Effects on Specialist and Generalist Insect Herbivores - Altesor, Paula (2014)
Plant domestication by selective breeding may reduce plant chemical defense in favor of growth. However, few studies have simultaneously studied the defensive chemistry of cultivated plants and their wild congeners in connection to herbivore susceptibility. We compared the constitutive glycoalkaloids (GAs) of cultivated potato, Solanum tuberosum, and a wild congener, S. commersonii, by liquid chromatography coupled to mass spectrometry. We also determined the major herbivores present on the two species in field plots, and tested their preference for the plants and their isolated GAs in two-choice bioassays. Solanum commersonii had a different GA profile and higher concentrations than S. tuberosum. In the field, S. tuberosum was mostly attacked by the generalist aphids Myzus persicae and Macrosiphum euphorbiae, and by the specialist flea beetle Epitrix argentinensis. In contrast, the most common herbivore on S. commersonii was the specialist sawfly Tequus sp. Defoliation levels were higher on the wild species, probably due to the chewing feeding behavior of Tequus sp. As seen in the field, M. persicae and E. argentinensis preferred leaf disks of the cultivated plant, while Tequus sp. preferred those of the wild one. Congruently, GAs from S. commersonii were avoided by M. persicae and preferred by Tequus sp. The potato aphid performed well on both species and was not deterred by S. commersonii GAs. These observations suggest that different GA profiles explain the feeding preferences of the different herbivores, and that domestication has altered the defensive capacity of S. tuberosum. However, the wild relative is still subject to severe defoliation by a specialist herbivore that may cue on the GAs.